Seletividade de herbicidas pós-emergentes associados a fertilizante foliar na cultura da soja - Alencar, Érica Silva de (2021)
Throughout the soybean crop cycle, the use of herbicides to control weeds is common, as well as the association of these products with foliar fertilizers. These mixtures, although widely used, can cause different effects, requiring further studies on these interactions. The objective of this work was to evaluate the selectivity of post-emergence herbicides associated with foliar fertilizer in soybean crop. The experiment was carried out at the Experimental Farm (FAECA) of the Federal University of Grande Dourados – UFGD, in a randomized block design, with four replications. The treatments applied were: chlorimuron (17.5 g ai ha-1 g ha-1 ai); chlorimuron + foliar fertilizer (17.5 + 693 g a.i. ha-1 ); chlorasulam (40 g a.i. ha-1 ); chlorasulam + foliar fertilizer (40 + 693 g a.i. ha-1 ); hungersafem (225 g a.i. ha-1 ); hungersafem + foliar fertilizer (225 + 693 g a.i. ha-1 ); glyphosate (1280 g a.i. ha-1 ); glyphosate + foliar fertilizer (1,280 + 693 g a.i. ha-1 ) and two controls, one with weeding and the other without weeding. Visual evaluations of phytotoxicity were carried out at 7, 14, 21, 28, 35 days after the first application of treatments (DAA). 1000 grains and moisture. After the analysis of variance by the F test and the mean of treatments compared by the Tukey test, it was concluded that the use of foliar fertilizers did not influence the symptoms of phytotoxicity in any of the treatments tested. In herbicides that inhibit the enzyme Acetolactate Synthase (ALS), the level of phytotoxicity was below 35%, while the inhibitors of the enzyme protoporphyrinogen oxidase (PROTOX) and the enzyme enol-pyruvylshikimate-phosphate synthetase (EPSPs) were below 5 %. In productivity, there was a significant difference only for the control without weeding (612.5 kg ha-1), when compared to the other treatments. There was no statistical difference in the weight of a thousand grains for the treatments tested. ALS-inhibiting herbicides show greater symptoms of phytotoxicity, and the lack of maintenance in the controls without weeding decreases productivity in the soybean crop.